PENERAPAN PENDEKATAN PEMBELAJARAN KONSTEKTUAL (CTL) PADA KOMPETENSI DASAR MENJELASKAN KONSEP PENAWARAN DAN PERMINTAAN UANG UNTUK MENINGKATKAN MOTIVASI DAN KETUNTASAN BELAJAR SISWA KELAS X-2 SMA NEGERI 1 MANTUP, LAMONGAN - RISKA AYUNINGTYAS (Universitas Negeri Surabaya, 2013)
This study aims to increase student motivation and exhaustiveness learning on the basis of competency describes the concept of supply and demand for money in the class X-2 SMA Negeri 1 Mantup Lamongan using contextual learning approach. This study was conducted in two cycles. Based on the analysis conducted can be seen that on the cycle 1 teachers activity earned an average of 2.78 and at cycle 2 increased to 3.60. The same with students activity in cycle 1 gained an average of 2.37 and at the cycle 2 increased to 3.63. Students' motivation also increased, before implementation of contextual learning approach, students' motivation was only 67.84%, but after the application of contextual learning approach students' motivation increased to 81.11%. At the same time the percentage of classical exhaustiveness learning at cycle 1 is 78.13%, in cycle 2 increased to 90.62%. This shows that the application of contextual learning approach on the basis of competency describes the concept of supply and demand for money can increase student motivation and exhaustiveness learning class X-2 student on SMA Negeri 1 Mantup Lamongan. Keyword: Contextual Learning Approach (CTL), Learning Motivation, Mastery Learning